2015
DOI: 10.1002/dys.1517
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement of University Students with Dyslexia

Abstract: Broadened recruitment to higher education is on the agenda in many countries, and it is also widely recognized that the number of dyslexic students entering higher education is increasing. In Sweden, as in many other European countries, higher education institutions are required to accommodate students with dyslexia. The present study focuses on the study outcome for 50 students with diagnosed dyslexia, mainly in teacher education and nurses' training, at three universities in Northern Sweden. The students tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 18 publications
4
49
0
3
Order By: Relevance
“…Challenges became evident across most aspects of university learning experiences for students with dyslexia. The patterns reported by students with dyslexia in this study broadly confirm and support those reported in previous research (Pino & Mortari, ; Olofsson, Taube, and Ahl, ), including difficulties with note‐taking, reading journal articles and course books, technology, accessibility and adjustments. Although some students will overcome these difficulties, the additional effort may lead to greater frustration and lower completion rates than might otherwise be expected.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Challenges became evident across most aspects of university learning experiences for students with dyslexia. The patterns reported by students with dyslexia in this study broadly confirm and support those reported in previous research (Pino & Mortari, ; Olofsson, Taube, and Ahl, ), including difficulties with note‐taking, reading journal articles and course books, technology, accessibility and adjustments. Although some students will overcome these difficulties, the additional effort may lead to greater frustration and lower completion rates than might otherwise be expected.…”
Section: Discussionsupporting
confidence: 90%
“…Positive themes included appreciation for engaging speaking style and flexible lecture formats, deep engagement with learning tasks and use of many self‐directed learning strategies that could be viewed as strengths. These findings are consistent with those of previous researchers (Kirby et al ., ; Pino & Mortari, ; Olofsson, Taube, and Ahl, ), who found that students with dyslexia used deep learning strategies more often than their non‐dyslexic peers and used more study aids and coping strategies. These types of characteristics and behaviours tend to be highly sought after in workplaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of timely rehabilitation and delayed or poorly effective treatments may have long-term effects on educational opportunities and vocational opportunities and success (Ghidoni & Angelini, 2011;Olofsson, Taube, & Ahl, 2015). As a result, the significant reading deficits of individuals with DD impact on daily life to such an extent that they may contribute to the high incidence of overlap with other psychological disorders (Huc-Chabrolle, Barthez, Tripi, Barthélémy, & Bonnet-Brilhault, 2010;Mammarella et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Þá hafa rannsóknir sýnt að háskólanemar sem eiga við námsvanda að stríða, svo sem vegna námserfiðleika, persónulegra erfiðleika eða tungumálaerfiðleika, standa frammi fyrir meiri hindrunum í námi en aðrir. Þeir eru lengur að ljúka háskólanámi, fá laegri einkunnir og eiga fremur á haettu að hverfa frá námi en aðrir nemendur (Advokat, Lane og Luo, 2011;Budd, Fichten, Jorgensen, Havel og Flanagan, 2016;Erten, 2011;Newman o.fl., 2011;Olofsson, Taube og Ahl, 2015).…”
Section: áHrifaþaettir í Námiunclassified